The development of school graduation exam in mathematics in 1998–2003 - Narkevičienė, Bronė; Stričkienė, Marytė (Lietuvos matematikos rinkinys, 2003)
The aim of the article is to discuss the developmet of school graduation exam of mathematics in the past 5 years (1998–2003), refering to the problems started 5 years ago and the objectives of the examination. The analysis of the results of 1999 and 2003 examination in mathematics showed that the reliability of the exam has increased, howewer, the most difficult tasks remain the tasks of the same subject both in 1999 and 2003.